Tribute to Professor Clive Emsley - Lawrence, Paul (Crime, histoire & sociétés, 2021)
Clive Emsley was one of the foremost exponents of criminal justice history, a long-standing contributor to this journal and a constant friend to many members of its Editorial Board. A generous and inclusive scholar, with a vast store of knowledge and a prodigious tally of influential publications, he helped to define and develop criminal justice history from the 1970s onwards, encouraging and nurturing a new generation of researchers along the way.